Blazing saddles - Brooks, Mel, 1926-; Hertzberg, Michael; Bergman, Andrew; Little, Cleavon; Wilder, Gene, 1933-2016.; Pickens, Slim.; Huddleston, David, 1930-2016.; Starrett, Jack, 1936-1989.; Kahn, Madeline; Korman, Harvey, 1927-2008.; Biroc, Joseph, 1903-1996.; Greene, Danford B.; et al. (Burbank, Calif. : Warner Home Video, 2004)
A hilarious spoof of every western film cliche in which a black man is appointed sheriff of a frontier town.
Originally released as 1974 motion picture by Warner Bros.
Special features: Scene-specific commentary by Mel Brooks; "Back in the saddle" documentary; "Intimate portrait : Madeline Kahn remembers"; "Black Bart", the 1975 TV pilot inspired by the movie; additional scenes; theatrical trailer.
Director of photography, Joseph Biroc ; editors, Danford Greene and John C. Howard ; music, John Morris.
Mel Brooks, Cleavon Little, Gene Wilder, Slim Pickens, David Huddleston, Claude Ennis Starrett Jr., Madeline Kahn, Harvey Korman.
MPAA rating: R.
DVD; NTSC, region 1; widescreen presentation; Dolby surround, Dolby Digital 5.1.
Keywords: African American police -- West (U.S.) -- Drama; Railroad companies -- Drama; West (U.S.) -- Ethnic relations -- Drama; Comedy films; Feature films; Video recordings for the hearing impaired